(untitled) (Baltic Journal of Sport and Health Sciences, 2016)
Background. The purpose of this study was to identify whether the learning effect, fatigue, motivation, effort and/or sex-specific neural, physiological and morphological factors influenced the results of the test–retest reliability of tests to assess cognitive function. Methods. The sample included ten men (age 21.2 ± 0.4 years; body mass 79.5 ± 8.3 kg) and ten women (age 22.0 ± 1 years; body mass 60.0 ± 10.0 kg). Participants accomplished six tests (three for memory and three for attention) four times, i.e. two times (with 24 hours’ break) on successive days (teaching) and two times (with 48 hours’ break) on the third and fifth days (re-testing to assess the reliability). The reliability was assessed by calculating the average of the population, standard deviation, and intraclass correlation coefficient (ICC). Results. In males and females, measurements of attention function were highly reliable over time (ICC > .84). The ICCs for volume of spatial memory were above .79, for memory of even number recognition above .57 for both genders and for memory of figure recognition .00 for males and .79 for females. Conclusion. In young healthy males and females, measurements of attention function were highly reliable over time. Meanwhile, reliability for volume of spatial memory was good/high for both sexes, but reliability of memory for even number recognition was insufficient for both sexes and results from memory of figure recognition showed good reliability for women and insufficient reliability for men. Keywords: memory, attention, test-retest, reproducibility, gender.